A retrospective evaluation of the NHS Health Check Programme in a multi-ethnic population. (17th October 2016) - Carter, P.; Bodicoat, D.H.; Davies, M.J.; Ashra, N.B.; Riley, D.; Joshi, N.; Farooqi, A.; Browne, I.; Khunti, K.
Abstract : Background: The NHS Health Check Programme was introduced in 2009 to improve primary prevention of coronary heart disease, stroke, diabetes and chronic kidney disease; however, there has been debate regarding the impact. We present a retrospective evaluation of Leicester City Clinical Commissioning Group. Methods: Data are reported on diagnosis of type 2 diabetes, hypertension, chronic kidney disease, high risk of type 2 diabetes and high risk of cardiovascular disease. Data on management following the Health Check are also reported. Results: Over a 5-year period, 53 799 health checks were performed, 16 388 (30%) people were diagnosed with at least one condition when diagnosis of being at high risk of cardiovascular disease was defined as ≥20%. This figure increased to 43% when diagnosis of high cardiovascular risk ≥10% was included. Of the 3063 (5.7%) individuals diagnosed with type 2 diabetes, 54% were prescribed metformin and 26% were referred for structured education. Of the 5797 (10.8%) individuals diagnosed at high risk of cardiovascular disease (≥20%), 64% were prescribed statins. Conclusions: A high proportion of new cases of people at risk of cardiovascular disease were identified by the NHS Health Check Programme. Data suggest that this has translated into appropriate preventative measures.